Kebebasan Berserikat dan Keamanan Negara: Analisa Biopolitik Transformasi Kebebasan Serikat Buruh di Indonesia - Azhiim, Rizma Afian; Bastari, Gema Ramadhan (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2018)
In general, there are two assumptions often associated with the Indonesian labor movement in the Reformation Era: (1) the labor movement inhibits the production process and the investment climate by conducting demonstrations and/or strikes and (2) the labor movement constantly makes unreasonable demands, generally attributed to wage increases demands. This paper attempts to position these assumptions as irrelevant and also potentially lead to backward thinking in seeing how the labor movement struggles to achieve prosperity for all Indonesian workers. Through biopolitical analysis, this paper tries to explain that giving workers the right to association will not threaten national security, as long as freedom of association can be regulated and directed to ensure the survival of labor, the conducive social relations of production, and the improvement of the living conditions of society to sustain the economic system. The analysis in this paper has led to the finding that the demands provided by the labor movement are part of the corrective mechanisms of the production system in Indonesia, and the freedom of labor to associate is an essential factor that can guarantee economic and political security as well as the sovereignty of the Indonesian state.